Long-term impact of biochar on the immobilisation of nickel (II) and zinc (II) and the revegetation of a contaminated site - Shen, Zhengtao; Som, Amelia Md; Wang, Fei; Jin, Fei; McMillan, Oliver; Al-Tabbaa, Abir (Science of The Total Environment, 2016)
A field remediation treatment was carried out to examine the long-term effect of biochar on the immobilisation of metals and the revegetation of a contaminated site in Castleford, UK. The extracted concentrations of nickel (Ni) (II) and zinc (Zn) (II) in the carbonic acid leaching tests were reduced by 83–98% over three years. The extracted Ni (II) and Zn (II) concentrations three years after the treatment were comparable to a cement-based treatment study carried out in a parallel manner on the same site. The sequential extraction results indicated that biochar addition (0.5–2%) increased the residue fractions of Ni (II) (from 51% to 61–66%) and Zn (II) (from 7% to 27–35%) in the soils through competitive sorption, which may have resulted in the reduction of leachabilities of Ni (II) (from 0.35% to 0.12–0.15%) and Zn (II) (from 0.12% to 0.01%) in the plots with biochar compared with that without biochar three years after the treatment. The germination of grass in the plots on site failed. Further laboratory pot study suggested that larger amounts of biochar (5% or more) and compost (5% or more) were needed for the success of revegetation on this site. This study suggests the effectiveness and potential of biochar application in immobilising heavy metals in contaminated site in the long term.